Pengaruh Media Paper Plate Terhadap Fisik Motorik Halus Pada Anak Usia Dini - Rina Syafrida; Ega Trisna Rahayu; Dinda Nur Akmalia (Universitas Singaperbangsa Karawang, 2022)
paperplate media is an option that can be used to explore more activities that can be used for child development. Paperplate media is easy to find in the area around Karawang so that it is easy to reach, easy and safe to use for children, and can be created to be used as various types of activities. Keywords: Paper plate, motoric, childhood